Franciscan virtue spiritual growth and the virtues in Franciscan literature and instruction of the thirteenth century - Pansters, Krijn, 1975- (Leiden ; Boston : Brill, 2012)
Providing an in-depth analysis of the virtues of evangelical life according to three major Franciscan authors, this book is a valuable contribution to our understanding of how the virtues functioned as central, organizing elements in early Franciscan literature and instruction.
Virtue -- Virtues -- The virtue of virtue -- The virtues in the opuscula sancti Francisci Assisiensis -- Bibliographical overview -- Instances of habitus datus.
Includes bibliographical references.
Description based on print version record.
Keywords: Franciscans -- History; Spiritual formation; Virtue; Church history -- Middle Ages, 600-1500.; Church history -- Middle Ages, 600-1500.; Franciscans -- History; Spiritual formation; Virtue; Religion; RELIGION / Christian Life / General; Electronic books